New imaging approaches for precision diagnosis and disease staging of MS?. (April 2020) - Oh, Jiwon; Sicotte, Nancy L
Magnetic resonance imaging (MRI) has revolutionized the diagnosis and management of people living with multiple sclerosis (MS). However, conventional MRI sequences and measures currently used in clinical practice have limitations in the appropriate diagnosis, prediction of future disability, and monitoring of disease activity in MS. A specific challenge is the accurate and timely diagnosis of progressive subtypes of MS. This article will summarize emerging MRI measures that may be of utility as clinical tools in diagnosis and prediction in MS. Although a wide range of MRI techniques have different strengths and weaknesses, those that will be discussed in this article include the "central vein sign, " leptomeningeal inflammation/enhancement, conventional and quantitative spinal cord imaging, susceptibility-weighted imaging, and high-field MRI techniques. There are a number of novel and emerging MRI techniques that hold promise in improving diagnosis, prediction, and disease monitoring in MS.